USAHA KECIL KRUPUK IKAN GABUS DI DUSUN KAUMAN SURABAYA - Chandra Kartika; Chamariyah; Rena Febrita Sarie (LPPM Universitas PGRI Adi Buana Surabaya, 2022)
The purpose of this PPM activity is to help business actors of Krupuk Ikan Gabus SME Partners to provide understanding to business actors about the factors supporting business activities, namely legality and business management factors so that business activities carried out are not only profit-oriented, but business activities can continue to develop in the future by paying attention to and applying supporting factors for business activities. The specific objectives are: so that partners of Krupuk Ikan Gabus Products can earn income from the results of the products they make in order to be able to work on the economy with maximum achievements in accordance with the problems or problems that partners do. Furthermore, in order to be able to raise the level of his life in living his life. The target of this PPM Activity at this Snakehead Fish Product Partner is to make Employee SOPs, training on making Simple Financial reports, Making new Krupuk Packaging, Helping Digital Marketing so that income increases, Coaching and training employees for hygenic product production, training and coaching on management in good inventory and business management, helping to make logos, media banners and pamlets for advertising. The method implemented in this Community Empowerment Program is through business mentoring techniques including partner mindset coaching, business capital assistance online marketing training, training and financial report coaching, product promotion assistance, quality and quality snakehead fish krupuk production assistance, business management training, and training on selecting the most desirable krupuk flavors. The results of the Community Empowerment Program activities significantly increased the income and productivity of this group of community partners higher before, significantly understanding the business knowledge well, starting from good production, very fast sales and digital marketing as well as improvements in hygenic science in the management of these krupuk products.